Group Affiliation and Default Prediction - Beaver, William H.; Cascino, Stefano; Correia, Maria; McNichols, Maureen F. (Management Science, 2019)
Using a large sample of business groups from more than 100 countries around the world, we show that group information matters for parent and subsidiary default prediction. Group firms may support each other when in financial distress. Potential group support represents an off-balance sheet asset for the receiving firm and an off-balance sheet liability for the firm offering support. We find that subsidiary information improves parent default prediction over and above group-level consolidated information possibly because intragroup exposures are netted out upon consolidation. Moreover, we document that improvements in parent default prediction decrease in the extent of parent-country financial reporting transparency, a finding that suggests that within-group information matters most when consolidated financial statements are expected to be of lower quality. We also show that parent and other group-firms’ default risk exhibits predictive power for subsidiary default. Lastly, we find that within-group information explains cross-sectional variation in CDS spreads. Taken together, our findings contribute to the prior literature on default prediction and have direct relevance to investors, credit-rating agencies, and accounting regulators. This paper was accepted by Suraj Srinivasan, accounting.